Pre‐operative Functional Parameters of Patients Undergoing Total Knee Arthroplasty. (27th February 2015) - Tambascia, Rafael Andrade; Vasconcelos, Rodrigo Antunes; Mello, Wilson; Teixeira, Paulo Portes; Grossi, Debora Bevilaqua
Abstract: Background and purpose: Total knee arthroplasty (TKA) has become the gold standard to manage pain and disability associated with knee osteoarthritis (KOA). There are no clear criteria on to determine when or who should undergo TKA. The creation of a pre‐operative profile that includes physical functional data may aid in the clinical decision‐making for the timing of TKA. Aim 1: to observe the pre‐operative functional profile of subjects with advanced KOA and to depict it according to gender. Aim 2: to assess the association between pain, self‐reported and performance‐based physical function outcomes. Materials and methods: Study design: retrospective study. Physical functional data from 122 persons (89 women and 33 men) with end‐stage KOA were obtained through a database. Data consisted of height, weight, 6‐minute walk test (6MWT) and the deficit when compared with normative values, self‐visual analogue scale (VAS) after 6MWT and Western Ontario and McMaster Universities Index (WOMAC). Descriptive statistics were used to report the observed data; student t ‐test and Mann–Whitney were used to compare gender groups. Spearman correlation was used to asses the association with the 6MWT, WOMAC and VAS. Results: The mean (standard deviation) values of our sample for the WOMAC, 6MWT deficit and VAS were calculated. There was a significant difference between gender in the WOMAC score and pain intensity (VAS) after the 6MWT ( p = 0.002; p = 0.01). Moderate to weak correlations between WOMAC score, VAS and 6MWT were found. Correlation values ranged from r = 0.23 to 0.48. Conclusion: The current study suggests a functional profile for subjects who are scheduled to undergo TKA. Our results show that the correlations of self‐report and performance‐based measures of function and reported pain are poor. This enhances the idea of using all of these types of measures to establish the functional profile a sample of subjects with advanced KOA. Copyright © 2015 John Wiley & Sons, Ltd.